Computerised decision support in veterinary medicine, exemplified in a canine idiopathic epilepsy care pathway. (21st June 2021) - Fox, K.; Fox, J.; Bexfield, N.; Freeman, P.
Abstract : Computerised decision support is of emerging and increasing importance in human medicine, but as yet has not been thoroughly applied or evaluated in veterinary medicine. In this essay, the authors report on the first example of a veterinary care pathway, a specific form of computerised decision support, which guides clinicians through a clinical workflow and incorporates individual patient data to inform patient‐specific decision recommendations. The veterinary care pathway was designed using consensus statements and specialist neurologist opinion to create a decision support tool concerning canine idiopathic epilepsy. The authors evaluated the care pathway by comparing 35 clinical decisions made by referral clinicians in historical cases of idiopathic epilepsy to decisions recommended by the care pathway when presented with the same clinical case. Their results show that in 77.1% (95% confidence interval [59.9, 89.6]) of cases the care pathway recommended a decision that was the same or similar to a specialist neurologist's decision. Whilst further studies are needed to explore the potential use of such technology in clinical practice, the authors believe this first application provides great promise of a new and alternative method of clinical decision support.